Significant correlations between the flow volume of patent ductus venosus and early neonatal liver function: possible involvement of patent ductus venosus in postnatal liver function. Issue 3 (31st January 2006) - Murayama, K; Nagasaka, H; Tate, K; Ohsone, Y; Kanazawa, M; Kobayashi, K; Kohno, Y; Takayanagi, M
Abstract : Background: The biochemical features of portosystemic venous shunt with high flow volume are hypergalactosaemia, hyperammonaemia, prolonged blood coagulation time, and raised serum bile acid concentration. The ductus venosus remains open with shunt flow in most neonates for a certain period after birth. However, the effects of blood flow through the ductus venosus on neonatal liver function remain unclear. Objective: To elucidate the effect of patency of the ductus venosus on liver function in early neonates. Methods: Subjects were divided into three groups by gestational age (group I, 29–32 weeks; group II, 33–36 weeks; group III, 37–41 weeks). The shunt flow volume through the ductus venosus was examined serially using ultrasonography, and correlations between flow volume and liver function in the respective groups were calculated during the first week after birth. Results: Group I had a higher flow volume and later functional closure than the other two groups. Plasma ammonia and serum total bile acid concentrations correlated with flow volume in groups I and II, and blood galactose and galactose 1-phosphate concentrations correlated significantly with flow volume in group III. Percentage hepaplastin also correlated significantly with flow volume in all groups, but plasma vitamin K concentration did not in any group. Conclusions: Patent ductus venosus has a considerable effect on crucial liver functions such as ammonia detoxification, blood coagulation, and regulation of serum total bile acid concentration in early neonates.